Economic discrimination and cultural differences as barriers to migrant integration: Is reverse causality symmetric? - Pierre Kohler (Graduate Institute of International and Development Studies, 2012)
This paper examines the endogenous relationship between the economic and cultural integration of migrants in Switzerland or, more precisely, how economic and cultural barriers to integration reinforce each other. Are cultural differences preventing the successful integration of migrants or does the root of integration failures lie in unequal economic opportunities and discrimination? How legitimate are claims arguing migrants are economically discriminated because they don't integrate culturally compared to claims that migrants don't integrate because they are discriminated? And are Muslim communities, which currently often lie at the center of this debate, different in this regard? Implementing an empirical method to build indices of economic discrimination and cultural differences (cultural distance), the findings of this paper show that, at the aggregate level, population groups facing higher economic discrimination are culturally more distant from the natives. Muslim communities are no different in this regard: their specificity resides more in the stronger discrimination they face in the labour market than in cultural differences separating them from natives. Using an instrumental variable approach, evidence at the individual level reveals that there is an asymmetric causal relationship between economic discrimination and cultural distance, the former clearly dominating the latter. It also shows that the asymmetry is at least twice as acute for secondgeneration compared to first-generation migrants.
Keywords: F22; J15; J31; J60; J68; J71; Z10; Z13; 330; migration; labor market; unemployment; muslim; religious; ethnic; discrimination; culture; integration; Migranten; Soziale Integration; Ethnische Diskriminierung; Araber; Ethnische Beziehungen; Schweiz